Choline chloride/urea as an effective plasticizer for production of cellulose films. (6th March 2015) - Wang, Sha; Peng, Xinwen; Zhong, Linxin; Jing, Shuangshuang; Cao, Xuefei; Lu, Fachuang; Sun, Runcang
Highlights: A novel plasticizer ChCl/urea was found to effectively plasticize cellulose films. ChCl/urea showed good compatibility with cellulose. No chemical reaction and crystallization occurred to ChCl/urea plasticized cellulose film. ChCl/urea was comparable to glycerol and sorbitol, and could be used as a potential plasticizer for cellulose film. Abstract: Recently, choline chloride/urea (ChCl/urea), a typical deep eutectic solvent (DES), has been found to possess various applications in organic synthesis, electrochemistry, and nanomaterial preparation. Herein we reported the first attempt to plasticize regenerated cellulose film (RCF) using ChCl/urea as an effective plasticizer. Meanwhile, RCFs plasticized with glycerol and sorbitol were also prepared for comparison. The plasticized RCFs were investigated by Fourier transform infrared (FT-IR) spectroscopy, wide-angle X-ray diffraction (XRD), atomic force microscopy (AFM), and mechanical testing. Transparent and soft RCFs could be successfully prepared in the presence of ChCl/urea, and high elongation at break (34.88%) suggested a significant plasticizing efficiency. No new crystal and phase separation occurred to ChCl/urea plasticized RCFs. The thermal stability of ChCl/urea plasticized RCF was lowered. These results indicated that ChCl/urea was an effective plasticizer for producing cellulose films.